Influences of surface treatment on In0.53Ga0.47As epitaxial layer grown on silicon substrate using trimethylaluminum - Kim, Soo Bin; Lee, Seung Hyun; Jung, Hae Jun; Seo, Myung Su; Kim, Sung Min; Lee, Soonil; Park, Ji Yong; Park, Tae Joo; Jeong, Hae Yong; Jun, Dong Hwan; Park, Kyung Ho; Park, Won Kyu; et al. (Thin Solid Films, 2018)
A development of high quality InxGa1 − xAs epitaxial layers on Si substrates is essential for high-performance logic transistors due to the low fabrication cost and high compatibility with a conventional Si technology. We investigate the surface of In0.53Ga0.47As epitaxial layers grown by metal-organic chemical vapor deposition on a Si substrate (with InP/GaAs buffer layers) to obtain a high capacitance using high-k films (HfO2/Al2O3 bilayer). The high-k films were grown on In0.53Ga0.47As epitaxial layers by atomic layer deposition (ALD). The interface between the high-k bilayer and the In0.53Ga0.47As epitaxial layer was analyzed depending on a surface treatment of the In0.53Ga0.47As epitaxial layer, and the surface treatment of the In0.53Ga0.47As epitaxial layer using trimethylaluminum (TMA) enhanced the electrical performances of Pt/high-k film/In0.53Ga0.47As capacitors. The TMA was introduced on the In0.53Ga0.47As epitaxial layer in the ALD chamber, which reduced native oxides (such as gallium and arsenic oxides) of the In0.53Ga0.47As surface and minimized a formation of interfacial layers between the high-k film and In0.53Ga0.47As layer. A capacitance equivalent thickness (CET) of ~ 1.5 nm was achieved with a low leakage current (~ 10− 4 A/cm2 at 1 V). A CET as low as ~ 1.3 nm and a capacitance > 2.5 μF/cm2 was attained by optimizing the high-k/In0.53Ga0.47As interface. The TMA treatment on the In0.53Ga0.47As epitaxial layer is compatible with the conventional Si technology and provides promising opportunities for the development of state-of-the-art field-effect transistor technology using InxGa1 − xAs epitaxial layers.
Keywords: Capacitance density; Capacitance-equivalent thickness; Electrical performance; High- k; High-performance logic; Indium gallium arsenide; Low-leakage current; Trimethylaluminum; Atomic layer deposition; Capacitance density; Dielectric constant; Epitaxial layer; High-k; Indium gallium arsenide; Silicon; Trimethylaluminum